Adaptation to the Spanish university context and psychometric properties of the MSLQ: Contributions to the measurement and analysis of gender differences of self-regulated learning - Cardeñoso Ramírez, Olga; Larruzea-Urkixo, Nerea; Bully Garay, Paola (Anales de Psicología / Annals of Psychology, 2022)
A challenge in advancing research into self-regulated learning in general, and gender differences in particular, is related to the measurement of various components and self-regulatory processes of it. Therefore, this study aims to adapt into Spanish and analyzes 1) the internal structure, reliability, and gender invariance of the Motivated Strategies for Learning Questionnaire (MSLQ) and 2) the differences between males and females in the MSLQ dimensions and subdimensions. Participants consisted of 428 university students (73.7% women). Results showed that this adaptation is shorter than the original and has better metric properties than other versions. Also, invariance analysis showed that for men and women, the instrument possesses a common structure and loads (metric invariance) that guarantees valid score comparisons by gender. Moderate to high differences were found in women’s favor in the value given to homework, different learning strategies, and anxiety before examinations. This study responds to the need for a culturally adapted, valid, and reliable instrument in Spain and delves into gender differences in self-regulated learning, a key building block to successfully develop academic training at the present times.